Literature and legal discourse : equity and ethics from Sterne to Conrad - Polloczek, Dieter (Cambridge University Press, 1999)
"Polloczek analyses the links between actual legal fictions such as substituted judgements, notions of equity, literary tropes, and the construction and representation of social bonds through sentiment, philanthropy and marginalization. Polloczek's study is both theoretical and historical, covering a period that extends from the eighteenth century to the modernist period, and includes texts from Sterne, Bentham, Dickens and Conrad."--Jacket